Agricultural trade: What matters in the doha round? - Laborde Debucquet, David; Martin, Will (Annual Reviews, 2012)
This survey concludes that including agriculture in the negotiations was particularly important economically. Although agricultural exports are less than 10% of merchandise trade, the high and variable protection in this sector appears to account for the majority of the cost of distortions in global merchandise trade. Within agriculture, most of the costs appear to arise from trade barriers levied on imports, because these barriers tend to be high and variable across products and over time and are levied by many countries that do not use subsidies. The diverse interests of participants resulted in very complex proposals and a tendency for countries to focus on the political costs of an agreement, rather than on the potential economic benefits. The negotiations faced a need for balance between discipline in reducing tariffs and flexibility in managing political pressures. Although the approach of providing flexibilities on a certain percentage of tariff lines is seriously flawed, the proposed modalities still appear to provide worthwhile market access. There need to be better ways of dealing with developing countries’ concerns about food price volatility while reducing the collective-action problems resulting from price insulation.